RESEARCH PROGRESS ON THE FOUR-IN-ONE METHOD SYSTEM FOR SUSTAINABLE PROTECTION OF ARCHITECTURAL HERITAGE - Y. Chi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
With the development of social economy, the definition, scope and connotation of architectural heritage have also evolved. However, the architectural heritage is facing the threat of destruction and destruction. The sustainable protection of architectural heritage has become a major strategic need of the country to enhance cultural self-confidence. In the past century, the concept of architectural heritage protection has evolved many times. At present, preventive protection and research protection have become the consensus in the field of architectural heritage protection. The idea of preventive protection is to delay the destruction or extinction of architectural heritage by controlling the main factors that cause the changes in the ontology. Preventive protection is different from emergency protection after the destruction of architectural heritage. It mainly discovers and eliminates hidden dangers through scientific records, periodic inspection, systematic monitoring and routine maintenance. It emphasizes the analysis of damage evolution law through risk assessment and scientific monitoring and takes effective protection measures. Based on the concept of preventive protection and research protection, combining the accumulation of prior art development and protection practices, this paper proposes a four-in-one sustainable preservation method system for architectural heritage. It mainly includes four aspects: architectural heritage value and protection demand cognition, all-round information access technology, architectural heritage monitoring and evaluation, architectural heritage performance improvement and value continuation.